Неуловимая коллекция: повесть / В. Б. Гусев - Гусев Валерий Борисович (Детский детектив, 2000)
Экземпляры: аб. (2000) / Инвентарный номер: 42171 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 96 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44